2007
DOI: 10.1111/j.1475-6773.2007.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Outcomes and Evidence‐Based Medicine in a Preferred Provider Organization Setting: A Six‐Year Evaluation of a Physician Pay‐for‐Performance Program

Abstract: Objective. To determine whether health plan members who saw physicians participating in a quality-based incentive program in a preferred provider organization (PPO) setting received recommended care over time compared with patients who saw physicians who did not participate in the incentive program, as per 11 evidence-based quality indicators. Data Sources/Study Setting. Administrative claims data for PPO members of a large nonprofit health plan in Hawaii collected over a 6-year period after the program was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…147 Studies for as long as 6 years show that appropriately selected incentives can maintain physician satisfaction, patient satisfaction, and long-term performance. 148 Incentives also reinforce the office team structure. 149 Oversight is essential to the ultimate success of a patient centered medical home system of care.…”
Section: Reimbursement Modelsmentioning
confidence: 99%
“…147 Studies for as long as 6 years show that appropriately selected incentives can maintain physician satisfaction, patient satisfaction, and long-term performance. 148 Incentives also reinforce the office team structure. 149 Oversight is essential to the ultimate success of a patient centered medical home system of care.…”
Section: Reimbursement Modelsmentioning
confidence: 99%
“…However, given the limited size of the incentives implemented in P4P to date, one can ask whether evaluation results showing no impact or limited impact of P4P are a fair test of this new approach to provider payment. Indeed, recent evidence has shown more positive effects of P4P, although studies have found that the effect size remains modest in most cases and the largest effects are often for provider organizations and physicians that have started at lower levels of performance Felt-Lisk et al, 2007;Gilmore et al, 2007;Glickman et al, 2007;Grossbart, 2006;. One review suggests that incentives of about 5 percent of total physician earnings are large enough to attract "meaningful attention" from physicians (Young et al, 2007).…”
Section: Magnitude and Risk Of Financial Incentivesmentioning
confidence: 99%
“…For example, some programs have provided incentives for health care professionals to invest in information technology, implement electronic health records (EHRs), or use EHRs. These programs include the Integrated Healthcare Association, Bridges to Excellence, and the Hawaii Medical Services Association (IOM Board on Health Care Services, 2007; Bridges to Excellence, 2008;Gilmore et al, 2007;McDermott et al, 2006).…”
Section: Structure Measuresmentioning
confidence: 99%
See 2 more Smart Citations